Flotation of rare earth minerals from silicate–hematite ore using tall oil fatty acid collector. (April 2016) - Satur, Jacqueline V.; Calabia, Buenaventurada P.; Hoshino, Mihoko; Morita, Sayaka; Seo, Yuna; Kon, Yoshiaki; Takagi, Tetsuichi; Watanabe, Yasushi; Mutele, Litshedzani; Foya, Stewart
Highlights: Tall oil fatty acids floated RE minerals from silicates and hematite at basic pH. RE grade improved with sodium metasilicate + sodium fluoride or starch as depressant. Similar selectivity curves by the depressants suggest REM incomplete liberation. High RE recoveries but low RE grades in the froths were obtained. Liberation of RE minerals is important in achieving selective separation. Abstract: The flotation of rare earth (RE) minerals (i.e. xenotime, monazite-(Nd), RE carbonate mineral) from an ore consisting mainly of silicate minerals (i.e. primary silicate minerals and nontronite clay) and hematite was investigated using tall oil fatty acids (Aero 704, Sylfat FA2) as collector. The RE minerals are enriched with Fe. The effects of tall oil fatty acid dosage, pH, temperature, and conventional depressants (sodium lignin sulfonate, sodium metasilicate, sodium fluoride, sodium metasilicate and sodium fluoride, and soluble starch) were determined at grinding size of P80 = 63 μm. At this grinding size, the grain size of the RE minerals ranges from 2 to 40 μm, percentage liberation is 9–22%, and percentage association with nontronite and quartz is 30–35%. Results indicated that Sylfat FA2 at 22450 g/t concentration was the more efficient tall oil fatty acid collector at natural pH (pH 7) to basic pH (pH 10.0–11.5). Flotation at the room temperature (25 °C) gave higher selectivity than 40 °C temperature flotation. The results on the effect of depressants showed similar selectivity curves against the gangues SiO2, Al2 O3, and Fe2 O3 suggesting that the chemical selectivity of the depressants has been limited by the incomplete liberation of the RE minerals in the feed sample. High recoveries at 76–84% (Y + Nd + Ce)2 O3 but still low (Y + Nd + Ce)2 O3 grade at 2.1% in the froth were obtained at flotation conditions of 63 μm, 25 °C, pH 10.5, 1, 875 g/ton sodium metasilicate and 525 g/ton sodium fluoride or 250 g/ton soluble starch as depressant for the silicates and hematite, and 22, 450 g/t Sylfat FA2 as collector for the RE minerals (initial (Y + Nd + Ce)2 O3 feed grade = 0.77%). The recoveries of gangue SiO2, Al2 O3, and Fe2 O3 in the froth were low at 25–30%, 30–37%, and 30–36%, respectively. The mineralogical analysis of a high grade froth and its corresponding tailing product showed that the RE minerals have been concentrated in the froth while the primary silicate minerals and hematite have been relatively concentrated in the tailing. However, the clay minerals, primary silicate minerals, and hematite still occupy the bulk content of the froth. This suggests that incomplete liberation of the RE minerals led to the poor grade result, supporting likewise the selectivity curve results by the different depressants. This study showed that liberation is important in achieving selective separation.